Pengaruh Program CHSE terhadap Citra, Kepercayaan, Kepuasan, dan Loyalitas Pengunjung pada Masa Pandemi Covid-19 di DTW Pantai Melasti Ungasan Bali - Diarta, I Ketut Surya (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
Implementation of the Cleanliness, Health, Safety, and Environmental Sustainability (CHSE) program at the Melasti Beach Ungasan Bali tourist destination is intended to boost visitor trust. This study examined visitor views of the implementation of CHSE at Melasti Beach and the consequent effects on destination image, trust, satisfaction, and loyalty. SEMPLS assessed data gathered through the surveying of 100 respondents. CHSE is well-implemented, and visitors trust the destination. Visitors are incredibly satisfied and loyal to the site. CHSE improves visitor trust and satisfaction but does not affect a destination's image. Image influences visitor trust but not satisfaction. Visitors' loyalty is unaffected by visitors' trust. Visitor loyalty is highly influenced by visitor satisfaction. The data reveals that the CHSE program is still vital during the COVID-19 pandemic because it boosts tourist trust and satisfaction.